2019
DOI: 10.1002/cre2.192
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between T‐helper cell polarization and the RANKL/OPG ratio in gingival tissues from chronic periodontitis patients

Abstract: This study aimed to investigate the relationship between inflammation‐related T‐helper cell polarization and the receptor activator for nuclear factor‐κB ligand (RANKL)/osteoprotegerin (OPG) ratio, which is associated with bone resorption or remodeling of chronic periodontitis patients. Gingival crevicular fluid (GCF) and gingival tissues were obtained from periodontally healthy individuals (PH group) and chronic periodontitis patients (CP group). The GCF levels of IFN‐γ, IL‐4, IL‐17, and IL‐10 linked to T‐hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 60 publications
(71 reference statements)
5
37
1
Order By: Relevance
“…The pressure side, characterized by bone resorption, displays a high RANKL/OPG profile similar to that observed in chronic periodontitis, whereas the tension side, characterized by new bone formation, presents a RANKL < OPG profile similar to gingivitis sites (Menezes et al 2008). Accordingly, previous studies also described an increased RANKL/OPG ratio in periodontitis samples in comparison to healthy or gingivitis tissues, with increased RANKL levels associated with progressive tissue destruction (Bostanci et al 2007; Bi, Sun, et al 2019; Lopez Roldan et al 2020). Nevertheless, longitudinal prospective studies are required to further determine if a RANKL/OPG ratio comprises an effective biomarker of disease activity as described for other bone-related conditions.…”
Section: Lesion Progression Patterns: Evidence From Clinical and Labomentioning
confidence: 79%
See 1 more Smart Citation
“…The pressure side, characterized by bone resorption, displays a high RANKL/OPG profile similar to that observed in chronic periodontitis, whereas the tension side, characterized by new bone formation, presents a RANKL < OPG profile similar to gingivitis sites (Menezes et al 2008). Accordingly, previous studies also described an increased RANKL/OPG ratio in periodontitis samples in comparison to healthy or gingivitis tissues, with increased RANKL levels associated with progressive tissue destruction (Bostanci et al 2007; Bi, Sun, et al 2019; Lopez Roldan et al 2020). Nevertheless, longitudinal prospective studies are required to further determine if a RANKL/OPG ratio comprises an effective biomarker of disease activity as described for other bone-related conditions.…”
Section: Lesion Progression Patterns: Evidence From Clinical and Labomentioning
confidence: 79%
“…Indeed, while IFN-γ and IL17 can amplify host response by the induction of proinflammatory cytokines and mediate RANKL production by resident cells of periapical lesions, Th1 and Th17 responses can be mutually inhibitory (Colavite et al 2019; Duka et al 2019). In contrast, the simultaneous detection of high levels of both IL17 and IFN-γ in diseased periodontium is also described, suggesting a possible interplay toward disease progression (Dutzan, Gamonal, et al 2009; Bi, Sun, et al 2019; Sommer et al 2019). Considering that even cytokines that are routinely used as Th polarization surrogates (i.e., IFN-γ, IL17) can also be produced by other cell types and that Th plasticity has been described in periodontal tissues (with the occurrence of Tbet + IL10 + and FOXp3 + IL17 + cells) (Okui et al 2012), it becomes clear that comprehensive studies, not exclusively focused on a single mediator or cell subset, are required to unravel the immunological complexity underlying lesion progression.…”
Section: Host Response Determinants Of Lesion Progression and Stabilitymentioning
confidence: 99%
“…2019) and lower concentrations of the anti‐inflammatory cytokine, IL‐10 (Bi et al . 2019). Hoppe et al .…”
Section: Discussionmentioning
confidence: 99%
“…258,259 Bi et al reported increased T H 1/T H 17 cells in periodontitis-afflicted gingival isolates, whereas T H 2/T regulatory cells were upregulated in healthy gingiva. 260 Serotype b of A. actinomycetemcomitans induced elevated T-bet + interferon-gamma + and RAR-related orphan receptor gamma t + interleukin-17 + T cells in periodontal lesions, which were associated with increased RANKL and alveolar bone resorption. 258 Capsular-defective mutant strains of P. gingivalis promoted less bone loss and decreased T H 1/T H 17 cells and related cytokines compared with the encapsulated W50 wild-type strain.…”
Section: Whereas Early Investigations Evaluated the T H 1/t H 2 Balanmentioning
confidence: 99%
“…Monasterio and coworkers recently employed the murine oral inoculation periodontitis model to show that the T H 1/T H 17 immune response and periodontal bone loss is strain dependent 258,259 . Bi et al reported increased T H 1/T H 17 cells in periodontitis‐afflicted gingival isolates, whereas T H 2/T regulatory cells were upregulated in healthy gingiva 260 . Serotype b of A. actinomycetemcomitans induced elevated T‐bet + interferon‐gamma + and RAR‐related orphan receptor gamma t + interleukin‐17 + T cells in periodontal lesions, which were associated with increased RANKL and alveolar bone resorption 258 .…”
Section: Osteoimmunology: Interaction Of Immune Cells: Bone Cellsmentioning
confidence: 99%